Digital Audit as a Solution to Data Security Challenges in the Era of Digital Transformation - Mitrah Andira; Andika Rusli; Andi Dahri (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the role of digital audits as a solution to data security challenges in the era of digital transformation, with a case study of the Palopo City Communication and Informatics Agency (Kominfo) in 2025. In the context of implementing an Electronic-Based Government System (SPBE), data security is a crucial aspect that demands systematic oversight through digital audits. Methodology: This study uses a qualitative method with a case study approach, involving two key informants from the IT field to gain an in-depth understanding of digital audit implementation, security strategies, and regulatory compliance. Results: The results show that digital audits play a crucial role in ensuring data confidentiality, integrity, and availability through the implementation of firewalls, VPNs, layered authentication systems, structured backups, and the use of technology-based audit tools. In addition to technical aspects, digital audits also strengthen compliance with regulations such as the Personal Data Protection Law (UU PDP) and the National Cyber and Crypto Agency (BSSN) guidelines. Findings: The findings confirm that digital audits serve as a strategic instrument for maintaining data security and enhancing institutional accountability. Novelty & Originality: This study offers novelty by examining digital audit implementation in a local government context in Palopo City, an area rarely explored in prior research. Conclusions: In conclusion, digital audits have proven to be a strategic instrument for maintaining data security and increasing public trust in government digital services, while also serving as an implementation model that can be replicated by other agencies in the era of digital transformation. Type of Paper: This paper is an empirical research paper.